Penerapan Strategi Marketing Mix (Bauran Pemasaran) Pada UMKM Pondok Ikan Bakar Aru Lubeg - Adi Purnama; Akhdiat Oktrinaldo; Bayu Amanda; Vicky Brama Kumbara (STIKes Ibnu Sina Ajibarang, 2024)
In line with the development of the era of science and technology, the pace of culinary business development is running rapidly. development of the culinary business is running at a rapid pacePadang is a city that Padang is a city that has tourist attractions that are often visited by tourists, with the many tourist attractions that exist make more and more MSMEs grow in the city of Padang. Padang, so that the emergence of businesses such as Pondok Ikan Bakar Aru Lubeg, this business is a good opportunity for Pondok Ikan Bakar Aru Lubeg. This is a good opportunity for Pondok Ikan Bakar Aru Lubeg to market its products. research is interested in How is the implementation of the marketing mix strategy in developing a business? which was carried out by Pondok Ikan Bakar Aru Lubeg? With the aim to identify and analyze the right marketing mix strategy for Pondok Ikan Bakar in order to achieve several main targets: 1. IncreaseSales: Increase the sales volume of grilled fish through effective marketing strategiesmarketing strategy. 2. Increased Consumer Awareness: Increase consumer awarenessawareness about the existence of Pondok Ikan Bakar as an attractive culinary destination. destination. 3. Brand Awareness Development: Building a strong and positive brand imagepositive in the eyes of consumers